The relationship between exponent t in McLachlan equation and electronic percolation thresholds of solution cast films - Xu, Huagen; Qu, Muchao; Chen, Baoquan; Yang, Qiancheng; Schubert, Dirk W. (Journal of Polymer Research, 2022)
To better understand the relationship between the exponent t in McLachlan's GEM equation and the percolation threshold of conductive polymer composites, in this work, a series of percolation threshold and exponent t pairs were obtained from the percolation curves of different carbon-based fillers utilizing the McLachlan equation. In particular, pairs derived perpendicular and in-plane to the films for binary composite films with carbon fiber of different aspect ratios (AR) as well as pairs derived perpendicular for ternary composite films with different polymer blends and different polymer blend ratios for both carbon black and carbon nanotubes filler were investigated. In these systems, the exponent t for all three fillers is different from the value of 2.0 often referred to as “universal”. Scanning electron microscopy was used to reveal the microscopic morphology of different shape fillers in the solution cast composite films. A schematic diagram was used to illustrate the differences in the conductive pathways formed by different conductive fillers.
CRIS-Team Scopus Importer:2022-11-04
Keywords: Carbon-based fillers; Conductive polymer composite films; Exponent t; McLachlan GEM equation; Percolation thresholds